Trends in quality-adjusted skill premia in the United States, 1960-2000 - Pedro Carneiro; Sokbae Lee (Institute for the Study of Labor (IZA), 2010)
This paper presents new evidence that increases in college enrollment lead to a decline in the average quality of college graduates between 1960 and 2000, resulting in a decrease of 6 percentage points in the college premium. We show that although a standard demand and supply framework can qualitatively account for the trend in the college and age premia over this period, substantial quantitative adjustments still need to be made to account for changes in quality.
Keywords: J0; 330; inequality; college premium; composition effects; Bildungsverhalten; Bildungsniveau; Akademiker; Bildungsertrag; Lohn; USA